2022
DOI: 10.1136/bmjgh-2021-007116
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of a large-scale home visiting programme (PIM) on early child development in Brazil: quasi-experimental study nested in a birth cohort

Abstract: BackgroundA large-scale parenting programme with weekly home visits (Primeira Infância Melhor (PIM)) has been implemented in the south of Brazil for nearly two decades, but lacks evaluation of its effects on early childhood development (ECD). This quasi-experimental study aimed to assess the effects of PIM in real-life settings within a population-based birth cohort study.MethodsData from the 2015 Pelotas Birth Cohort Study and the state programme information system were linked to identify study children who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Primary data from the 2015 Pelotas birth cohort were linked with PIM state database based on the child’s name, mother’s name and child’s DOB in order to evaluate the effects of PIM on participants in the cohort. PIM funding is contingent on the number of children registered per city, so it is unlikely families received the programme without being registered 24…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary data from the 2015 Pelotas birth cohort were linked with PIM state database based on the child’s name, mother’s name and child’s DOB in order to evaluate the effects of PIM on participants in the cohort. PIM funding is contingent on the number of children registered per city, so it is unlikely families received the programme without being registered 24…”
Section: Methodsmentioning
confidence: 99%
“…PIM became a public policy by law in 2006 and served as a model for Brazil’s federal parenting programme, Crianca Feliz (CF), which is the largest home-visiting programme in the world 27. Previous studies have found that children who received PIM demonstrated small reductions in infant mortality28 and school-reported behaviour problems29 and improvements in cognitive development 24. This is the first peer-reviewed evaluation of its kind to assess PIM’s effect on parent behavioural mechanisms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Quantitatively, individual studies have focused on program characteristics such as delivery modality and age of infant at enrollment, with little evidence that these implementation features are associated with program effectiveness in improving parent or child outcomes. 2,14,15 Indeed, quantitative analysis of program characteristics associated with the engagement of families and child and parent outcomes has often been restricted due to limited numbers of studies reporting implementation characteristics. 16 The few meta-analyses examining implementation characteristics have focused on intended dosage (i.e., duration 2 and intensity 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to contextual features, common programmatic features found in effective parenting interventions (e.g., supportive supervision) have been qualitatively identified 13 . Quantitatively, individual studies have focused on program characteristics such as delivery modality and age of infant at enrollment, with little evidence that these implementation features are associated with program effectiveness in improving parent or child outcomes 2,14,15 . Indeed, quantitative analysis of program characteristics associated with the engagement of families and child and parent outcomes has often been restricted due to limited numbers of studies reporting implementation characteristics 16 .…”
Section: Introductionmentioning
confidence: 99%